Digital display monitor performance in general dental practice. (20th May 2015) - Butt, A; Savage, NW
Abstract: Background: The performance of computer displays represents an important factor influencing the quality of digital radiographs. The aim of this study was to evaluate the performance of computer displays used for the purposes of diagnostic radiology in a sample of dental practices in one Australian state. Methods: Twelve dental practices comprising 29 displays elected to participate in a detailed performance evaluation of their computer displays according to the AAPM TG18 and DICOM part 14 GSDF standards. Results: None of the 29 displays tested passed the primary or secondary acceptance criteria developed by the AAPM TG18. The greatest contributor to display failure, both prior to and following calibration, were specular and diffuse reflection. When the parameter of display reflection was ignored, the most frequent parameters contributing to display failure following calibration included the primary grade acceptance criteria of noise (n = 29, 100%), contrast ratio (n = 9, 31%) and maximum luminance (n = 12, 41%). However, display calibration resulted in a significant improvement in the parameter of contrast response. Conclusions: This study demonstrated significant problems concerning the performance of display monitors in the population surveyed. In recognition of the growing utilization of digital imaging in dentistry the importance of the computer display should be considered.